Increased Dietary Energy in Limit-fed Diets Does Not Affect Immune Function, Inflammation, or Stress, but Health Status Does - T. J. Spore; S. P. Montgomery; E. C. Titgemeyer; G. A. Hanzlicek; Christopher Vahl; T. G. Nagaraja; W. R. Hollenbeck; R. N. Wahl; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2018)
Objectives:Measure effects of limit-feeding high-energy diets on the immune system, stress, and inflammation as well as differences in these parameters between healthy and sick animals under the dietary conditions. Study Description:Heifers from 4 dietary treatments were used to study the effects of limit-feeding and increased dietary energy on immune function, inflammation (indicated by elevated levels of haptoglobin), stress, and differences in these parameters between healthy and morbid animals consuming the different diets. The Bottom Line:Limit-feeding high-energy diets does not negatively affect immune function, cause stress, or promote inflammation, and morbid animals have significantly higher haptoglobin levels.
Keywords: Stocker cattle; limit-feeding; health